The role of CCN family genes in haematological malignancies - Wells, J.; Howlett, M.; Cheung, Laurence; Kees, U. (2015)
Haematological malignancies, although a broad range of specific disease types, continue to show considerable overlap in classification, and patients are treated using similar chemotherapy regimes. In this review we look at the role of the CCN family of matricellular proteins and indicate their role in nine haematological malignancies including both myeloid and lymphoid neoplasms. The potential for further haematological neoplasms with CCN family associations is argued by summarising the demonstrated role of CCN family genes in the differentiation of haematopoietic stem cells (HSC) and mesenchymal stem cells. The expanding field of knowledge encompassing CCN family genes and cancers of the HSC-lineage highlights the importance of extracellular matrix-interactions in both normal physiology and tumorigenesis of the blood, bone marrow and lymph nodes.